Pelepasan Ibuprofen dari Gel Karbomer 940 Kokristal Ibuprofen-Nikotinamida - Rini Agustin; Novica Sari; Erizal Zaini (Fakultas Farmasi Universitas Andalas, 2014)
One of the methods to increase the solubility is co-crystalization. As Ibuprofen can be used in topical application for rheumatoid arthritis, a study about formulation and release of ibuprofen-nicotinamide co-crystal in carbomer gel had been conducted. Co-crystal was obtained from a dissolve method, which ibuprofen and nicotinamida were mixed with equimol composition (1:1). Gel consisted of two formulas with the same amount of ibuprofen (5%). The first formula was gel co-crystal ibuprofen-nicotinamide and the second formula was pure ibuprofen. The basis used was carbormer 940. The release test was done using the horizontal type of Franz diffusion cell and measured using HPLC (High Performance Liquid Chromatography) with mobile phase of methanol: aquabidest (80:20) pH 3.5 with orthophosphate acid. The results showed both formulas were not stable in homogeneity aspect for several storage days. Separation was occurred at low and high temperatures. The result of release profiles at the 120th minutes was 4.4793 % and 4.4293 % and the release efficiencies were 3.8891 and 3.8612. The statistic analysis showed that release efficiencies of both formulas were not significantly different (p>0.05) using One-Way ANOVA. In a conclusion, the process of making gel of co-crystal ibuprofen-nicotinamide did not influenced ibuprofen release in gel preparation.